Public Sphere Concept Education in Society for Student Executive Board Hang Tuah Tanjungpinang Health Science College - Ibnu, Cian; Ikha Rahardiantini; Lili Sartika; Masyitah Novia Yanti; Aulia Chintara Wanda (GoResearch - Research & Publishing House, 2024)
The concept of public sphere according to Hannah Arendt is a sphere built by distinctive elements, namely from human and social conditions, namely Vita Acktiva. Through this formulation, humans are defined as creatures who are always active. Both mental activities and sensory activities. Whether it is inner action or real action. Human life that thinks, wants and considers is included in mental actions or inner actions of humans. While the life of human activity working, creating and speaking is included in real actions or speech. An action or behavior that is able to build a world together with fellow humans. The results of this community service activity are that participants understand the values ​​contained in public sphere. The conclusion of this community service activity shows an increase in knowledge and attitudes of educational participants about public sphere. All participants are enthusiastic about following the activity material from the beginning to the end and are actively discussing intensively in following the entire educational process.